Emergent visions : adjacency and urban screens - Kang, Kristy H. A. (2019)
Emergent Visions gathers a group of international artists, curators, and scholars for dialogue and thoughtful critique concerning the diverse frames and practices through which we might recognize the emergent and evocative visions, affects, and practices potentiated in and around urban screens. Hosted by The School of Art, Design and Media at Nanyang Technological University, with support and collaboration from Indiana University and the School of Arts, Technology, and Emerging Communication at University of Texas Dallas, this symposium provides a platform for expanding our conceptions of mediated public space, and for developing modes of inquiry that reflect upon, and even challenge how we might newly engage with these spaces and surfaces – from various scales and contexts and with great sensitivity to a range of perspectives.